2012
DOI: 10.1073/pnas.1217323110
|View full text |Cite
|
Sign up to set email alerts
|

Amphipathic antenna of an inward rectifier K + channel responds to changes in the inner membrane leaflet

Abstract: Membrane lipids modulate the function of membrane proteins. In the case of ion channels, they bias the gating equilibrium, although the underlying mechanism has remained elusive. Here we demonstrate that the N-terminal segment (M0) of the KcsA potassium channel mediates the effect of changes in the lipid milieu on channel gating. The M0 segment is a membrane-anchored amphipathic helix, bearing positively charged residues. In asymmetric membranes, the M0 helix senses the presence of negatively charged phospholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(112 citation statements)
references
References 44 publications
(61 reference statements)
11
101
0
Order By: Relevance
“…However, it appears hardly possible that the TM2 helix, which is hidden in the interior of KcsA, contributes to channel–channel interactions. Another structural element that responds to the closed‐to‐open transition is the membrane‐associated M0 helix, formed by the N‐terminal residues M1–G21 17. Indeed, it seems much more likely that M0 helices are involved in cluster formation, given that they are by far the most protruding element of the KcsA channel in the membrane plane.…”
mentioning
confidence: 99%
“…However, it appears hardly possible that the TM2 helix, which is hidden in the interior of KcsA, contributes to channel–channel interactions. Another structural element that responds to the closed‐to‐open transition is the membrane‐associated M0 helix, formed by the N‐terminal residues M1–G21 17. Indeed, it seems much more likely that M0 helices are involved in cluster formation, given that they are by far the most protruding element of the KcsA channel in the membrane plane.…”
mentioning
confidence: 99%
“…47,69) Such a big variation in channel activity was not anticipated by a change in lipid composition.…”
Section: Fig 6 the Cbb Methodsmentioning
confidence: 99%
“…Accordingly, the PG in the membrane inner leaflet keeps the KcsA channel active. 47,69) Further mutational study introduced into the N-terminal M0 helix elucidated that the positively charged residues on the M0 helix are responsible for the electrostatic interaction with the negatively charged lipid head groups in the inner leaflet. Fluorescence study revealed a novel mechanism of lipid sensing, such that the amphipathic M0 helix revolves around the helix axis upon opening and closing of the activation gate (the roll-and-stabilize mechanism).…”
Section: Fig 6 the Cbb Methodsmentioning
confidence: 99%
See 2 more Smart Citations